Standard static tests in conjunction with hopkinson bars - Ye, Zi (2015)
To study the mechanical properties of materials help us understand their merit and limitation in application. Hence, we can make better use of it and prevent failure in the future. Aluminum and Acrylic are both widely used elements in our daily life. The student carried out standard static tests for both tensile and compressive behavior analysis of these two materials. Others had conducted the standard static tensile test for Aluminum AL6061-T6 in the past. However, this year the student tried to add in strain gauge for measurement is a step forward. In addition, these results were further compared with dynamic test. A lot of standard static tests were prepared base on metallic materials, inspection of plastic material was introduced in this report also. Both standard static tensile test and compression test of Aluminum AL6061-T6 and Acrylic were accomplished by using INSTRON 5500R machine. The student used ASTM international standard as reference and the guide from seniors to set up the whole experiment. Then successfully collected the data to generate stress and strain curve for examination. The student found that the use of strain gauge did not really effect on the results of elastic modulus but better accuracy of tensile strain. However, using strain gauge easily made mistakes due to it high sensitivity. Some recommendations were provided in the end of this report, for example carry out Non Destructive Test for experiment specimen in case the internal defect effect on testing result.